SIMULASI WACANA MEDIA DAN PERMAINAN WACANA POLITIK - Goncing, Muh. Abdi; Syahrul, Fathullah (JPP (Jurnal Politik Profetik), 2021)
This article aims to analyze how the media does the simulate discourse in reality and to reveal how the media through their discourse play a political role in social life. The critical perspective of Jean Baudrillard's simulation theory is used as the basic approach for this research. The results of the research indicate that the media discourse through its simulation process has carried out the construction of reality which led to the establishment of a certain ideology that can stimulate the emergence of various needs that must be met by the audience. This need is then used by the media into forms of artificial reality which then directs the audience's perspective and political activities into virtual spaces. This political virtuality then creates a certain political ideology in the context of the audience's political life.